The role of leadership in establishing a positive staff culture in a secondary school. (September 2020) - Morris, Julia E; Lummis, Geoffrey W; Lock, Graeme; Ferguson, Cath; Hill, Susan; Nykiel, Annette
This Australian case study explored the implementation of strategies to support the development of a positive school culture among whole school staff. A participatory action research approach was used to involve leadership staff in the development of a mixed method assessment of the school organisation. Baseline data from the School Organisational Health Questionnaire ( n = 28) and qualitative data from focus groups ( n = 15) were collected and presented to the leadership team who identified four foci for the study: appraisal and recognition, participative decision-making, professional growth and supportive leadership. After a range of interventions, findings from both post-test surveys ( n = 22) and qualitative data ( n = 30) suggested a change in leadership style was a key factor of school cultural change across all factors. The case study highlights a number of visible strategies that were employed to increase morale and improve staff wellbeing.